2006
DOI: 10.1101/gad.1372606
|View full text |Cite
|
Sign up to set email alerts
|

A systematic search for downstream mediators of tumor suppressor function of p53 reveals a major role of BTG2 in suppression of Ras-induced transformation

Abstract: Factors that mediate p53 tumor suppressor activity remain largely unknown. In this study we describe a systematic approach to identify downstream mediators of tumor suppressor function of p53, consisting of global gene expression profiling, focused short hairpin RNA (shRNA) library creation, and functional selection of genetic elements cooperating with oncogenic Ras in cell transformation. This approach is based on our finding that repression of gene expression is a major event, occurring in response to p53 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 77 publications
3
110
1
Order By: Relevance
“…First, we confirmed that mycoplasma infection in fact resulted in decreased p53-dependent transcription of p21 waf1 in REF52 cells as it did in the other cell lines tested above (Figure 4a). Next, we prepared a variant of REF52 cells (REF52/sh-p53) in which p53 expression is reduced due to lentiviral transduction of shRNA against p53 (Boiko et al, 2006). shRNA-mediated knockdown of p53 expression was confirmed by semiquantative RT-PCR analysis of p53 mRNA levels (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…First, we confirmed that mycoplasma infection in fact resulted in decreased p53-dependent transcription of p21 waf1 in REF52 cells as it did in the other cell lines tested above (Figure 4a). Next, we prepared a variant of REF52 cells (REF52/sh-p53) in which p53 expression is reduced due to lentiviral transduction of shRNA against p53 (Boiko et al, 2006). shRNA-mediated knockdown of p53 expression was confirmed by semiquantative RT-PCR analysis of p53 mRNA levels (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type p53 repressed CGS expression by mechanisms involving the p53 targets BTG2 and ATF3, previously described as involved in Ras-induced transformation. 29,30 ATF3 directly binds to the CGS promoters and represses their expression, while BTG2 interacts with H-Ras and represses its activity. 31 This effect may represent a novel suppressive function of wild-type p53.…”
Section: The P53 Pathway: From Normal To Tumor Cellsmentioning
confidence: 99%
“…Firstly, large-scale proteomic approaches may help identify splicing factors and their posttranslational modifications induced by Ca ++ signals. Secondly, whole genome RNA interference libraries have been developed recently and applied to whole genome loss-of-function screening of genes [215][216][217][218][219][220][221][222]. Screening for alternative splicing factors by RNAi has already been carried out in fly cells [215,216].…”
Section: Perspectivesmentioning
confidence: 99%